1997
DOI: 10.1128/jcm.35.12.3288-3291.1997
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Amplicor HIV-1 monitor test and the nucleic acid sequence-based amplification assay for quantitation of human immunodeficiency virus RNA in plasma, serum, and plasma subjected to freeze-thaw cycles

Abstract: The Amplicor HIV-1 Monitor test was compared to the nucleic acid sequence-based amplification (Nasba) assay system for the quantitation of human immunodeficiency virus (HIV) RNA in three different types of clinical samples: plasma, serum, and plasma subjected to freeze-and-thaw cycles. Each assay detected HIV RNA in the same 73 (90%) of 81 samples tested, and the quantitative results obtained with the two assays were significantly correlated. Both assays detected higher RNA levels in patients with CD4 ؉ cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 19 publications
2
10
0
1
Order By: Relevance
“…Spearman correlation coefficient analysis indicated that the overall changes in patient viral load patterns were highly correlative between the two assays (P Ͻ 0.001). These results were in agreement with several studies that found that the values obtained by the first-generation nucleic acid sequence-based amplification assay and the Amplicor reverse transcriptase PCR Monitor assay were most often comparable but significantly different from the values obtained with the Quantiplex assay (1,5,7,8,15,19,22,24).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Spearman correlation coefficient analysis indicated that the overall changes in patient viral load patterns were highly correlative between the two assays (P Ͻ 0.001). These results were in agreement with several studies that found that the values obtained by the first-generation nucleic acid sequence-based amplification assay and the Amplicor reverse transcriptase PCR Monitor assay were most often comparable but significantly different from the values obtained with the Quantiplex assay (1,5,7,8,15,19,22,24).…”
supporting
confidence: 91%
“…The NucliSens assay performance characteristics were determined by using HIV-1 RNA standards obtained from the AIDS Clinical Trials Group Virology Laboratories Quality Assurance Program (VQA). The VQA standards were serially diluted to yield the following standards (numbers in parentheses denote the number of times each standard was assayed over several independent test runs): 80 copies/ml (19), 100 copies/ml (20), 500 copies/ml (10), 1,000 copies/ml (8), 1,500 copies/ml (8), 3,000 copies/ml (20), 15,000 copies/ml (8), and 150,000 copies/ml (8). All standards were quantitated with the Nucli-Sens assay according to the manufacturer's instructions.…”
mentioning
confidence: 99%
“…The linearities of Monitor and Nu-cliSens assay were comparable from approximately 500 to 1,000,000 RNA copies/ml, although Monitor had superior linearity and sensitivity in the lower range and performed variably at RNA levels greater than 1,000,000 copies/ml. These results resemble those found in comparisons of Monitor with the previous generation NASBA assay, which has a lower detection limit of 1,000 RNA copies/ml (3,8). Both assays gave correlation coefficients and linear slopes close to unity when compared with the nominal RNA concentrations present in serially diluted samples.…”
supporting
confidence: 80%
“…To evaluate if the drop of 1 log in this fourth patient indicates that viral load is not stable at ¹20 ЊC, further data are needed. In this context, it is interesting to note that up to 3 freeze-thaw cycles at ¹70 ЊC do not significantly influence viral load values [24].…”
Section: Discussionmentioning
confidence: 97%